Structural, optical and sensing properties of CdS-NH2GO thin film as a dengue virus E-protein sensing material - Sheh Omar, Nur Alia (Elsevier, 2018)
Semiconductor nanoparticles, cadmium sulfide quantum dots composited with amine functionalized graphene oxide (CdS-NH2GO) were functionalized with specific monoclonal antibodies (IgM) based on surface plasmon resonance (SPR) optical sensor for the detection of dengue virus (DENV) E-protein. The SPR results suggested that DENV E-protein can be detected in the range 0.0001–10 nM with the binding affinity of 486.54 nM−1. The successful binding between antibodies and antigens in an immunoassay sensor was further confirmed by Raman, UV–vis spectroscopy and atomic force microscopy (AFM). The Raman studies showed the depletion of protein molecules in the region of 120–1000 cm−1, which gives an evidence for the binding of DENV E-proteins to the antibodies. From UV–vis spectra, the absorption band was red shifted upon binding of DENV E-protein. The AFM measurement further confirmed the interaction occurred between DENV E-protein and the Au/CdS-NH2GO/IgM sensor surface.